Benefits of Internationalisation of Higher Education through Mobility of Students and Academic Staff in Tanzania: Case of University of Dar es Salaam - Nziku, Constancia Nziku; Kahangwa, George Kahangwa; Mabagala, Stephen Mabagala (Papers in Education and Development, 2022)
This study explored the benefits of internationalisation through mobility of students and academic staff at the University of Dar es Salaam (UDSM). Qualitative research approach using a single holistic case study was employed With 31 participants. Semi-structured interviews, focus group discussions and documentary review were used to collect data which was then analysed thematically. Findings revealed, inter alia, that mobility of students and staff enhanced global knowledge acquisition, generation of income, international co-authorship and cultural exchange. It is recommended that in order to benefit more from internationalisation, internationally attractive programmes should be offered by institution, marketing strategies should be enhanced by exploring customers ' preferences and a conducive environment with facilities which meet the international standards should be established. Keywords: global knowledge, international collaboration, knowledge economy